정밀 후각기관 장치에 의한 올란자핀의 비강내 전달 - DAS ADITYA R; HOEKMAN JOHN D; SATTERLY KELSEY H; DASHEVSKY INNA (2020)
정신분열증 또는 양극성 장애를 앓고 있는 환자의 초조를 포함한 초조를 급성으로 치료하는 방법으로서, 초조를 앓고 있는 대상체에게 올란자핀을 포함하는 건조 제약 조성물을 소정의 유효 투여량으로 투여하는 것을 포함하고, 상기 투여량은, 비강내 투여 후에 (a) 적어도 30 ng/mL의 평균 피크 혈장 올란자핀 농도(Cmax)를 제공하며 (b) 올란자핀의 Cmax에 이르는 평균 시간(Tmax)을 0.5시간 미만이 되게 하는 비강내 전달 장치에 의해 투여되는, 방법들이 제공된다. 올란자핀의 비강내 전달에 적합한 건조 제약 조성물 및 장치가 제공된다. Methods are provided for acute treatment of agitation, including agitation in patients with schizophrenia or bipolar disorder, comprising administering to a subject with agitation an effective dose of a dry pharmaceutical composition comprising olanzapine, wherein the dose is administered by an intranasal delivery device that provides, following intranasal administration, (a) a mean peak plasma olanzapine concentration (Cmax) of at least 30 ng/mL, with (b) a mean time to Cmax (Tmax) of olanzapine of less than 0.5 hours. Dry pharmaceutical compositions and devices suitable for intranasal delivery of olanzapine are provided.